Geochemical characteristics of oil sands fluid petroleum coke. (January 2017) - Nesbitt, Jake A.; Lindsay, Matthew B.J.; Chen, Ning
Abstract: The geochemical characteristics of fluid petroleum coke from the Athabasca Oil Sands Region (AOSR) of northern Alberta, Canada were investigated. Continuous core samples were collected to 8 m below surface at several locations ( n  = 12) from three coke deposits at an active oil sands mine. Bulk elemental analyses revealed the coke composition was dominated by C (84.2 ± 2.3 wt%) and S (6.99 ± 0.26 wt%). Silicon (9210 ± 3000 mg kg −1 ), Al (5980 ± 1200 mg kg −1 ), Fe (4760 ± 1200 mg kg −1 ), and Ti (1380 ± 430 mg kg −1 ) were present in lesser amounts. Vanadium (1280 ± 120 mg kg −1 ) and Ni (230 ± 80 mg kg −1 ) exhibited the highest concentrations among potentially-hazardous minor and trace elements. Sequential extractions revealed potential for release of these metals under field-relevant conditions. Synchrotron powder X-ray diffraction revealed the presence of Si and Ti oxides, organically-complexed V and hydrated Ni sulfate, and provided information about the asphaltenic carbon matrix. X-ray absorption near edge structure (XANES) spectroscopy at the V and Ni K-edges revealed that these metals were largely hosted in porphyrins and similar organic complexes throughout coke grains. Minor differences among measured V and Ni K-edge spectra were largely attributed to slight variations in local coordination of V(IV) and Ni(II) within these organic compounds. However, linear combination fits were improved by including reference spectra for inorganic phases with octahedrally-coordinated V(III) and Ni(II). Sulfur and Fe K-edge XANES confirmed that thiophenic coordination and pyritic-ilmenitic coordination are predominant, respectively. These results provide new information on the geochemical and mineralogical composition of oil sands fluid petroleum coke and improve understanding of potential controls on associated water chemistry. Highlights: Oil sands fluid petroleum coke contains wide range of major, minor and trace elements. Most abundant elements potentially-hazardous elements were V and Ni. Compositional and mineralogical controls on V and Ni speciation were proposed. Organic, asphaltenic, porphyrin-like compounds dominate V and Ni speciation. Mobilization of V and Ni may be attributed to minor inorganic fraction.